Beware the patient with a headache in the accident and emergency department. Issue 1 (March 1989) - Fodden, D I; Peatfield, R C; Milsom, P L
Abstract : We have reviewed the 130 patients presenting to an accident and emergency (A & E) department with a headache, followed up for 2 years. These are infrequent attenders but we have found that there is a high incidence of serious neurological pathology (16%) in this group of patients. We suggest that patients presenting to the A & E department with headache should be thoroughly examined and investigated and in the absence of a definite benign diagnosis should at least be admitted for a period of observation.